Engaging Millenials in Organ Donation: Establishing an educational programme. (August 2017) - Surendrakumar, Veena; Ayorinde, John O.; Russell, Neil; Gibbs, Paul; Hossain, Mohammad A.
Abstract : Introduction: Educational awareness programmes in organ donation in the UK are centralised by NHS Blood and Transplant. These programmes are generically adult based, however do not target students in the 'millenial' population. Given that this cohort of adults nearing voting age are likely to engage in the electoral system in the imminent future, we commenced a pilot educational programme specifically gauged towards evaluating the opinions of millenials regarding ethical topics in organ donation and transplantation. Methods: Secondary schools in the East Anglia and London region were contacted. An ethics and case based tutorial was prepared and delivered to groups of 16 to 18 year old students. Opinion questionnaires were completed before and after the session as well as a follow-up questionnaire one week later. Organ donation remained the central theme and opinions were drawn from free text answers and qualitative summation. Results: Fortythree young adults (41 females, age range 16-18 years) participated in the school tutorials. We received a 91% response rate to the pre-session questionnaire (n = 39). Results found 21% were already registered on the organ donor register, 72% had previously spoken to their family about organ donation and 49% (n = 19) were aware of the need for family consent at donation. Interestingly, prior to the start of the session, 67% (n = 26) would have considered monetary procurement of an organ for transplantation. Following the session, attitudes had changed in 51% (n = 20). Qualitative feedback highlighted increased awareness of the UK NHS transplant pathway, the ethical decisions faced by transplanting teams and the current requirement for next of kin consent. 94% of follow-up questionnaire respondents (n = 17/18) had engaged with family and friends about the tutorial in the week following. Conclusion: This short educational programme is currently in its infancy. Early results have shown a higher level of complex understanding from this involved group of individuals currently overlooked by the government and found that this small cost-effective tutorial can stimulate a wider discussion at home and outside school. We have highlighted a need to enrol millenials from the secondary education population into a broader discussion about organ donation and transplantation. Gauging the opinion of these young adults may help dictate policy at both a local and national government level with regards to future donation campaign strategies.